Chambers of commerce as a Form of Business Representation in Poland: A Literature Review - Iryna MANCZAK; Justyna DĄBROWSKA (Communications of International Proceedings, 2025)
The article aims to present the chambers of commerce in Poland as a form of business representation. These chambers are an example of organisations that bring together entrepreneurs, and in their activities, they focus on important issues from the perspective of doing business. A review of the subject literature was conducted within the framework of the adopted research convention. It was decided to outline considerations of a conceptual nature, as well as from the point of view of filling a research gap. The article reviews legal and economic publications. A critical analysis and desk research method was used. The authors highlighted selected issues concerning the structure of enterprises in Poland in 2024. In the article, a classification of terms concerning chambers of commerce was made to present their areas of activity. The Polish Chamber of Commerce activities, an example of a key organisation representing the Polish business community, were also discussed. Based on the analyses conducted, there is a need to initiate a wide-ranging public debate and appropriate legislative actions dedicated to strengthening the position of chambers of commerce. This debate should also focus on specifying the tasks carried out by the chambers and their competencies, including developing a modern model of economic self-government in Poland. Another conclusion indicates that the chambers of commerce qualify as a social organisation, which consequently determines the basic areas related to the management of their activities and the identification of directions for future research.
Keywords: market institutions; economic chambers in Poland; economic self-government; Polish Chamber of Commerce